Gender differences among youth in volunteerism / Mohd Ramlan Mohd Arshad, Zaliha Hj Hussin and Mohd Nazir Rabun - Mohd Arshad, Mohd Ramlan; Hj Hussin, Zaliha; Rabun, Mohd Nazir (Universiti Teknologi MARA, Shah Alam, 2015)
The growing demand for services has resulted in the increasing demand for volunteers. The lack of an adequate number of volunteers has left many agencies and organizations with the inability to provide services that clients need or desire. Thus, it increases the urgency for volunteers with a high level of energy which suit to youth volunteers. This paper aims to explore the issue of volunteerism among youths in terms of gender differences as an antecedent. Methodologically, the paper employs a quantitative approach to test and prove the formulated hyphotesis on gender differences in this issue. It begins with an introductory background to address the issue of volunteerism and the scenario of volunteerism among youth in Malaysia in general. The paper then proceeds to capture the differences between male and female youth to volunteer. The main analysis in the paper employs descriptive and inferential statistics to study the differences in the level of volunteering behaviour between male and female youth volunteers. There are also suggestions regarding volunteerism among youth in Petaling Jaya with regards to gender differences.